2016
DOI: 10.1021/acs.jmedchem.6b00122
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Benzocycloalkane Derivatives Efficiently Blocking Bacterial Virulence for the Treatment of Methicillin-Resistant S. aureus (MRSA) Infections by Targeting Diapophytoene Desaturase (CrtN)

Abstract: Antivirulence strategies are now attracting interest for the inherent mechanism of action advantages. In our previous work, diapophytoene desaturase (CrtN) was identified to be an attractive and drugable target for fighting pigmented S. aureus infections. In this research, we developed a series of effective benzocycloalkane-derived CrtN inhibitors with submicromolar IC50. Analogue 8 blocked the pigment biosynthesis of three MRSA strains with a nanomolar IC50 value. Corresponding to its mode of action, 8 did no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 26 publications
1
31
0
Order By: Relevance
“…In parallel, to further explore the potency of 19 and expand upon efficient novel inhibitors with independent intellectual property rights, we started another design of 19 ‐derived CrtN inhibitors . On the basis of the discovery of benzofuran analogs and their SAR, we confirmed that the naphthyl group in 19 or its similar groups, such as benzofuran, was necessary for maintaining pigment inhibition by blocking the enzyme CrtN.…”
Section: Pigments Of Representative Colored Pathogens and Their Inhibmentioning
confidence: 91%
See 1 more Smart Citation
“…In parallel, to further explore the potency of 19 and expand upon efficient novel inhibitors with independent intellectual property rights, we started another design of 19 ‐derived CrtN inhibitors . On the basis of the discovery of benzofuran analogs and their SAR, we confirmed that the naphthyl group in 19 or its similar groups, such as benzofuran, was necessary for maintaining pigment inhibition by blocking the enzyme CrtN.…”
Section: Pigments Of Representative Colored Pathogens and Their Inhibmentioning
confidence: 91%
“…In parallel, to further explore the potency of 19 and expand upon efficient novel inhibitors with independent intellectual property rights, we started another design of 19-derived CrtN inhibitors. 91 On the basis of the discovery of benzofuran analogs and their SAR, we confirmed that the naphthyl group in 19 or its similar groups, such as benzofuran, was necessary for maintaining pigment inhibition by blocking the enzyme CrtN. Rather than replacing the naphthyl group of 19 with various heteroaromatic groups, we initially intended to switch the naphthyl moiety of 19 into some benzocycloalkane rings of different sizes to generate novel skeleton compounds, which resulted in the synthesis of the derivatives 30-32.…”
Section: The Discovery Of Crtn Inhibitorsmentioning
confidence: 99%
“…Today, a number of proteins are considered as promising drug targets for the development of antibiotics to treat staphylococcal infections. After extensive review of the literature for the last three years, the following proteins were considered as potential therapeutic drug targets for the development of antistaphylococcal agents: bacterial enoyl reductase (FabI) [3,4], transglycosylase (TGase) [5,6], sortase A [7][8][9][10][11][12][13], diapophytoene desaturase (CrtN) [14][15][16][17], type II topoisomerase [18][19][20][21], topoisomerase IV [22][23][24][25][26][27], filamentous temperature-sensitive protein Z (FtsZ) [28][29][30], UDP-N-acetylenolpyruvylglucosamine reductase (MurB) [31], lipoteichoic acid synthase (LtaS) [32], biotin protein ligase [33,34], peptide deformylase [35], Ser/Thr protein kinase STK1 [36], pentaerythritol tetranintrate reductase [37], peptide deformylase (PDF) [38,39], NorA efflux pump [40][41][42][43][44]…”
Section: Introductionmentioning
confidence: 99%
“…19 On the basis of the results above, we further designed and synthesized a series of novel benzofuran and benzocycloalkane CrtN inhibitors, from which the efficient derivatives 3 and 4 were obtained (Figure 1). 20,21 Moreover, analogue 4a displayed excellent potency in vitro (pigment inhibition: IC 50 = 1.9 nM, Figure 1) but was still limited by its strong inhibition of human Ether-a-go-go Related Gene (hERG), high required dosage, and moderate water solubility in subsequent investigations. 21 Therefore, in this study, a novel compound was designed and synthesized to overcome the defects of lead compound 4a.…”
mentioning
confidence: 99%
“…20,21 Moreover, analogue 4a displayed excellent potency in vitro (pigment inhibition: IC 50 = 1.9 nM, Figure 1) but was still limited by its strong inhibition of human Ether-a-go-go Related Gene (hERG), high required dosage, and moderate water solubility in subsequent investigations. 21 Therefore, in this study, a novel compound was designed and synthesized to overcome the defects of lead compound 4a. In addition, variable administrations and dosages were introduced for an actual evaluation of the efficiency of our new compounds against multidrug resistant S. aureus in vivo.…”
mentioning
confidence: 99%